Damage and population dynamics of the fall armyworm (Spodoptera frugiperda) in elite lines of corn - Ávila-Martinez, Daniel; Cervantes-Ortiz, Francisco; Rodríguez-Pérez, Gilberto; Gámez-Vazquez, Alfredo Josué; García-Rodríguez, J. Guadalupe; Mendoza-Elos, Mariano (Agronomía Mesoamericana, 2023)
Introduction. Spodoptera frugiperda has the ability to form large populations, and its high dissemination rate makes this species an economically impactful pest. Losses due to pests and diseases are estimated at 37 % of global agricultural production, with 13 % caused by insects. Objective. To evaluate the attack, establishment, and population dynamics of fall armyworm larvae in maize lines. Materials and methods. The study was carried out in the laboratories of the Instituto Nacional de Investigaciones Forestales Agrícolas y Pecuarias and the Instituto Tecnológico de Roque, located in Celaya, Guanajuato, in 2019. Manual sowing was performed, and when the seedlings reached V4 stage, twenty-five days after sowing, they were infested with IV instar larvae. Population dynamics were measured starting from day twenty-six, covering the entire biological cycle (eggs, larva I, larva II, larva III, larva IV, larva V, pupa, and adult). A completely randomized experimental design with ten genotypes and ten replicates was employed. Results. S. frugiperda instar stages that showed the highest variability in maize lines were larvae IV and V. The population dynamics exhibited differences among tolerant genotypes, with an accumulated population of four to seven larvae in stages IV and V, while susceptible genotypes showed seven to twenty-one larvae in stage IV and fourteen to twenty-one in stage V. The outstanding maize presented an accumulation of two to six larvae in stage IV and four to five in stage per plant. Conclusion. The highest variability was observed in S. frugiperda larval stages IV and V, occurring between 26 and 54 days after planting. In the tolerant maize genotypes up to seven larvae were found per plant, while the susceptible ones showed twenty-one caterpillars.